Quality and safety requirements for pharmacy-based vaccination in resource-limited countries - Kidanemariam G/Michael Beyene; Melaku Tileku Tamiru (Tropical Medicine and Health)
Abstract Pharmacy-based vaccination (PBV) programs have proven to be a promising strategy for improving vaccination coverage, particularly in resource-limited countries. These programs increase accessibility and convenience, increase vaccination rates, and benefit vulnerable populations. However, successful implementation requires addressing gaps in regulatory oversight, pharmacists training, inter-professional collaboration, and public awareness. With proper regulatory frameworks, advocacy, enhanced training programs, public education, and establishment of well-designed database, PBV can achieve outcomes comparable to high-resource settings. This commentary aims to inform stakeholders and offer practical recommendations to minimize risks while leveraging its benefits.